Robotic Cochlear Implant Surgery: Imaging-Based Evaluation of Feasibility in Clinical Routine - Auinger, Alice Barbara; Dahm, Valerie; Liepins, Rudolfs; Riss, Dominik; Baumgartner, Wolf-Dieter; Arnoldner, Christoph (Frontiers in Surgery, 2021)
Background: Robotic surgery has been proposed in various surgical fields to reduce recovery time, scarring, and to improve patients’ outcomes. Such innovations are ever-growing and have now reached the field of cochlear implantation. To implement robotic ear surgery in routine, it is of interest if preoperative planning of a safe trajectory to the middle ear is possible with clinically available image data. Methods: We evaluated the feasibility of robotic cochlear implant surgery in 50 patients (100 ears) scheduled for routine cochlear implant procedures based on clinically available imaging. The primary objective was to assess if available high-resolution computed tomography or cone beam tomography imaging is sufficient for planning a trajectory by an otological software. Secondary objectives were to assess the feasibility of cochlear implant surgery with a drill bit diameter of 1.8 mm, which is the currently used as a standard drill bit. Furthermore, it was evaluated if feasibility of robotic surgery could be increased when using smaller drill bit sizes. Cochlear and trajectory parameters of successfully planned ears were collected. Measurements were carried out by two observers and the interrater reliability was assessed using Cohen’s Kappa. Results: Under the prerequisite of the available image data being sufficient for the planning of the procedure, up to two thirds of ears were eligible for robotic cochlear implant surgery with the standard drill bit size of 1.8 mm. The main reason for inability to plan the keyhole access was insufficient image resolution causing anatomical landmarks not being accurately identified. Although currently not applicable in robotic cochlear implantation, narrower drill bit sizes ranging from 1.0-1.7 mm in diameter could increase feasibility up to 100%. The interrater agreement between the two observers was good for this data set. Discussion: For robotic cochlear implant surgery, imaging with sufficient resolution is essential for preoperative assessment. A slice thickness of less than 0.3 mm is necessary for trajectory planning. This can be achieved by using digital volume tomography while radiation exposure can be kept to a minimum. Furthermore, surgeons, who use the software tool, should be trained on a regular basis in order to achieve planning consistency.